2009
DOI: 10.1136/bjsm.2009.058701
|View full text |Cite
|
Sign up to set email alerts
|

The development of a walkability index: application to the Neighborhood Quality of Life Study

Abstract: Emerging evidence supports a link between neighbourhood built environment and physical activity. Systematic methodologies for characterising neighbourhood built environment are needed that take advantage of available population information such as census-level demographics. Based on transportation and urban planning literatures, an integrated index for operationalising walkability using parcel-level information is proposed. Validity of the walkability index is examined through travel surveys among areas examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
923
3
44

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,021 publications
(996 citation statements)
references
References 34 publications
26
923
3
44
Order By: Relevance
“…These findings are not surprising, as these particular walkability measures were originally developed as potential correlates of active transport. 24 It was found that low SES areas had higher scores for intersection density and land use mix that are known to be associated with walking for transport. 32,33 Increasing recreational walking may not be feasible in some low SES areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are not surprising, as these particular walkability measures were originally developed as potential correlates of active transport. 24 It was found that low SES areas had higher scores for intersection density and land use mix that are known to be associated with walking for transport. 32,33 Increasing recreational walking may not be feasible in some low SES areas.…”
Section: Discussionmentioning
confidence: 99%
“…Objective attributes included four components of walkability: residential density, intersection density, land use mix, and net retail area ratio. 24 They were determined for each participant within a 1-km road network buffer from their home using ArcGIS software (ESRI, Redlands, CA). Residential density was calculated as the density of private dwellings in residential parcels within or intercepted by the buffer (number/km 2 ).…”
Section: Outcome Variablementioning
confidence: 99%
“…Subjective Physical Activity Measurements PA was measured using the long version of the International Physical Activity Questionnaire (IPAQ), 30 a validated self-report measurement tool. 31 The PA dimension assessed was walking for transport (meeting the weekly PA recommendation of ≥150 min/week vs. walking ≤150 min/week).…”
Section: Physical Activity Measurementsmentioning
confidence: 99%
“…18 An adjusted formula of former research was used: (2×z−connectivity)+(z−population density). 19 Recreational area data were calculated as an index of three factors. First, the amount of green and open space available per person for each community; second, the accessibility of that green and open space, expressed by people living in a span of 400 m of that green and open space; and lastly, the population and building density.…”
Section: Samplingmentioning
confidence: 99%